2001
DOI: 10.1177/107602960100700106
|View full text |Cite
|
Sign up to set email alerts
|

G20210A Prothrombin Gene Mutation: Prevalence in a Recurrent Miscarriage Population

Abstract: Many recurrent pregnancy losses appear to have a thrombotic etiology. We have investigated the prevalence of the G20210A prothrombin gene mutation in 122 women with a history of three or more early (< or = 12 weeks gestation; n = 91), late (> 12 weeks gestation: n = 2), or mixed (n = 29) consecutive pregnancy losses. A control group of 66 healthy parous women with no history of thrombosis or miscarriage was also studied. Four heterozygotes that suffered only early pregnancy losses were detected in the patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Gene variants frequently associated with RPL are prothrombin A20210G and/or factor V Leiden. Prothrombin A20210G has been identified as a risk factor for pregnancy loss in several studies and has been associated mainly to early RPL [15][16][17][18][19]. On the other hand, factor V Leiden, which is responsible for more than 75% of inherited activated protein C resistance, is the more common inherited thrombotic risk factor associated to RPL [20][21][22].…”
Section: Inherited Thrombophilia and Pregnancy Lossmentioning
confidence: 99%
“…Gene variants frequently associated with RPL are prothrombin A20210G and/or factor V Leiden. Prothrombin A20210G has been identified as a risk factor for pregnancy loss in several studies and has been associated mainly to early RPL [15][16][17][18][19]. On the other hand, factor V Leiden, which is responsible for more than 75% of inherited activated protein C resistance, is the more common inherited thrombotic risk factor associated to RPL [20][21][22].…”
Section: Inherited Thrombophilia and Pregnancy Lossmentioning
confidence: 99%
“…Fatini 61 Wramsby 105 Altinitas 52 Mougiou 82 Pickering 113 Subrt 99 Carp 58 Pauer 88 Consensus ( 119 Three metaanalyses 129,135,136 also reported that there is insufficient evidence that these treatments reduce loss rates in women with RPL who do not have antiphospho lipid syndrome or support the routine use of these treatments in women with RPL. Other nonhealthrelated benefits of F5/ F2 testing have been proposed, including value of information (i.e., identifying a "cause" for the RPL or allowing for alternative reproductive options), 137 but no relevant studies were identified.…”
Section: Pasquiermentioning
confidence: 99%
“…The most commonly related to spontaneous abortions are the Factor V Leiden mutation G1691A, mutation in the promoter region of the prothrombin gene G20210A, and homozygosity of C677T mutation in the methylene tetrahydrofolate reductase (MTHFR) gene with general prevalence of 2-15%, 2-3%, and 11%, respectively. These mutations are associated with mild thrombotic risks, and their association with spontaneous abortion remains controversial Pickering et al, 2001;Rai et al, 2001;Hefler et al, 2004;Tranquilli et al, 2004;Coulam et al, 2006;Yenicesu et al, 2010). Mutations that affect genes for factors involved in the common pathway of the coagulation cascade and the fibrinolytic system, such as in Factor XIII, b Fibrinogen, and plasminogen activator inhibitor-1 (PAI-1), may also contribute to the thrombotic tendency (Coulam et al, 2006;Yenicesu et al, 2010).…”
mentioning
confidence: 99%